Advantage of variable-speed pumped storage plants for mitigating wind power variations: Integrated modelling and performance assessment. (1st March 2019) - Yang, Weijia; Yang, Jiandong
Graphical abstract: Highlights: A performance assessment of VSPSPs for mitigating wind power variations is done. A flexible method of integrated modelling for VSPSPs is presented and validated. The analysis combines technical and economic indicators based on timescale of seconds. The quantitative results show the power regulation rapidity of variable speed units. The work could support development of variable-speed pumped storage technology. Abstract: Developing the joint operation of hydro and variable renewable energy has emerged as a research trend, for handling the power variability. In recent years, variable-speed pumped storage plants (VSPSPs) have been proposed as an alternative to fixed-speed pumped storage plants, but VSPSPs require a higher investment cost for equipment. Hence, evaluating the advantages and demonstrating the value of VSPSPs are meaningful topics that have seldom been studied by quantitative analysis with a small timescale. In this paper, a performance assessment of VSPSPs in terms of power regulation for mitigating wind power variations is undertaken based on a timescale of seconds, and the assessment combines the analysis of physical features and the economic indicators regarding ancillary service markets. First, a numerical model integrating hydraulic-mechanical-electrical subsystems of VSPSPs with doubly fed induction machines is built with MATLAB/Simulink, and it is validated by on-site measurements of a Japanese VSPSP. Then, based on a Chinese VSPSP, a quantitative comparison between variable-speed units (VSUs) and fixed-speed units (FSUs) is conducted through four indicators based on ancillary service compensation in electricity markets in China and the USA. Twelve scenarios are investigated, including case studies based on measured wind power variations. The results show that the VSU outperforms the FSU by one order of magnitude in the aspect of power regulation performance: the maximum ratios between the VSU and the FSU of the four indicators (average of power difference, standard deviation of power difference, penalty energy, and power delay) are 3.92%, 7.85%, 3.92%, and 5.56%. VSUs not only stand out for contributing to power system stability but can also obtain a significantly higher assessment in the ancillary service of the electricity market from an economic perspective. These results could be an important source of support for the investment and development of variable-speed pumped storage technology.